The Use of Jarimatika and Abacus Learning Media on Students' Counting Skills - Murti, Hanifah Nursiska; Utomo, Arief Cahyo (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This research is a quantitative study with a student population of SDN 02 Alastuwo, and the research sample is class IIA and IIB. Researchers use test questions and documentation as research techniques. The data analysis technique used is the t-test, which previously carried out prerequisite tests: the balance test, normality test, and homogeneity test. This study aims to compare the use of Jarimatika media with the abacus media on the numeracy skills of second-grade students of SDN 02 Alastuwo. The results of the analysis showed that there was no difference between the use of Jarimatika media and abacus media on students' numeracy skills. The results of the t-test obtained tcount ttable, namely 0.943 1.669. The average score of students increased after the application of both media. The average value of students using the media of Jarimatika is 83.57 and the average value for using the abacus is 79.70. This shows that both media are equally effective in improving students' numeracy skills. This research can be used as a reference that the media of Jarimatika and the abacus are effective in increasing the ability to count.Penelitian ini merupakan penelitian kuantitatif dengan populasi siswa SDN 02 Alastuwo dan sampel penelitian yaitu kelas IIA dan IIB. Peneliti menggunakan soal tes dan dokumentasi sebagai teknik penelitian. Teknik analisis data yang digunakan yaitu uji t, yang sebelumnya dilakukan uji prasyarat yaitu uji keseimbangan, uji normalitas serta uji homogenitas. Tujuan penelitian ini adalah komparasi penggunaan media jarimatika dengan media sempoa terhadap kemampuan berhitung siswa kelas II SDN 02 Alastuwo. Hasil analisis diperoleh bahwa tidak terdapat perbedaan antara penggunaan media jarimatika dan media sempoa terhadap kemampuan berhitung siswa. Hasil uji t diperoleh thitung ttabel yaitu 0,943 1,669. Rata-rata nilai siswa meningkat setelah penerapan kedua media. Rata-rata nilai siswa menggunakan media jarimatika adalah 83,57 dan rata-rata dengan media sempoa adalah 79,70. Hal ini menunjukan bahwa kedua media sama-sama efektif dalam meningkatkan kemampuan berhitung siswa. Penelitian ini dapat digunakan sebagai referensi bahwa media jarimatika dan sempoa efektif dalam meningkatkan kemampuan berhitung.